Impact investing: a theory of financing social enterprises - Roth, Benjamin N. (Harvard Business School, 2020)
I present a model of financing social enterprises to delineate the role of impact investors relative to “pure” philanthropists. I characterize the optimal scale and structure of a social enterprise when financed by grants, and when financed by investments. The analysis yields two heuristics to guide impact investors. First, investments allow a financier to discipline inefficient spending. Second, investments may enable a social enterprise to exploit new opportunities for profit, and may increase the enterprise's scale relative to when grant financed. I quantify these heuristics for the case of Husk Power, a social enterprise that has received impact investment
10.2139/ssrn.3535731
Keywords: Graue Literatur; Impact Investing; Social Entrepreneurship; Finance; Investment; Mathematical Methods